Cigarette smoke exposure induces ROS-mediated autophagy by regulating sestrin, AMPK, and mTOR level in mice - Ana Lucia Bernardo Carvalho Morsch; Elvis Wisniewski; Thais Fernandes Luciano; Vitor Hugo Comin; Gustavo de Bem Silveira; Scherolin de Oliveira Marques; Anand Thirupathi; Paulo Cesar Silveira Lock; Claudio Teodoro De Souza (Taylor & Francis Group, 2019)
Many pathological conditions linked to cigarette smoking are caused by the production of reactive oxygen species (ROS). The present study was conducted to analyze the effect of ROS on the lungs of Swiss mice exposed to cigarette smoking, focusing on autophagy-mediated mechanisms, and investigate the involvement of SESN2, AMPK, and mTOR signaling. Mice were exposed to cigarette smoke (CS) for 7, 15, 30, 45, and 60 days; the control group was not exposed to CS. Only mice exposed to CS for 45 days were selected for subsequent N-acetylcysteine (NAC) supplementation and smoke cessation analyses. Exposure to CS increased the production of ROS and induced molecular changes in the autophagy pathway, including an increase in phosphorylated AMPK and ULK1, reduction in phosphorylated mTOR, and increases in SESN2, ATG12, and LC3B levels. NAC supplementation reduced ROS levels and reversed all molecular changes observed upon CS treatment, suggesting the involvement of oxidative stress in inducing autophagy upon CS exposure. When exposure to CS was stopped, there were decreases in the levels of oxidative stress, AMPK and ULK1 phosphorylation, and autophagy-initiating molecules and increase in mTOR phosphorylation. In conclusion, these results suggest the involvement of ROS, SESN2, AMPK, and mTOR in the CS-induced autophagic process in the lung.